Transcobalamin receptor deficiency in seven asymptomatic patients ascertained through newborn screening. Issue 4 (3rd January 2022) - Pappas, Kara B.; Younan, Marissa; Conway, Robert
Abstract: We report seven cases from our clinic with transcobalamin receptor deficiency (TCRD). None of our cases have experienced health issues or metabolic decompensation. All have experienced typical growth and development throughout childhood, with our oldest case now 10 years old. Every case has had normalization of initial biochemical abnormalities following parenteral hydroxocobalamin administration. Several cases had trace elevations of methylmalonic acid throughout childhood, all which normalized without further hydroxocobalamin administration. Population data from our state's newborn screening program suggest the incidence of TCRD is comparable to other metabolic disorders associated with elevations of C3 acylcarnitine including propionic academia, isolated methylmalonic academia and combined methylmalonic academia and hyperhomocysteinemia due to cobalamin metabolism disorders. Based on the generally benign nature of this condition, we assert that TCRD may be considered an incidental finding on newborn screen. However, additional long‐term data are needed to ascertain the long term outcomes of children identified with TCRD.